2019
DOI: 10.1038/s41436-019-0595-x
|View full text |Cite
|
Sign up to set email alerts
|

The Liberfarb syndrome, a multisystem disorder affecting eye, ear, bone, and brain development, is caused by a founder pathogenic variant in the PISD gene

Abstract: PurposeWe observed four individuals in two unrelated but consanguineous families from Portugal and Brazil affected by early-onset retinal degeneration, sensorineural hearing loss, microcephaly, intellectual disability, and skeletal dysplasia with scoliosis and short stature. The phenotype precisely matched that of an individual of Azorean descent published in 1986 by Liberfarb and coworkers.MethodsPatients underwent specialized clinical examinations (including ophthalmological, audiological, orthopedic, radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…While many disease‐causing genes have clear roles in skeletal development (e.g., those involved in NOTCH, WNT, TGFβ, or BMP signaling), the skeletal roles for other genes are not yet clear. For example, pathogenic variants in mitochondrial proteins can cause a skeletal dysplasia, which is surprising, since skeletal manifestations are uncommon for most mitochondrial disorders (Dikoglu et al, ; Girisha et al, ; Mehawej et al, ; Peter et al, ; Royer‐Bertrand et al, ). In addition, genes that do not encode proteins are also responsible for skeletal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…While many disease‐causing genes have clear roles in skeletal development (e.g., those involved in NOTCH, WNT, TGFβ, or BMP signaling), the skeletal roles for other genes are not yet clear. For example, pathogenic variants in mitochondrial proteins can cause a skeletal dysplasia, which is surprising, since skeletal manifestations are uncommon for most mitochondrial disorders (Dikoglu et al, ; Girisha et al, ; Mehawej et al, ; Peter et al, ; Royer‐Bertrand et al, ). In addition, genes that do not encode proteins are also responsible for skeletal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mutations that affect PE synthesis have been identified in several human autosomal-recessive disorders. In particular, mutations in PISD, the human counterpart of fly PSD, cause Liberfarb syndrome, which is a multisystem disorder affecting the eyes, ears, bone, and brain [ 22 ]. Studies in patient-derived fibroblasts revealed impaired phospholipid metabolism, altered mitochondrial respiration, and fragmentation of the mitochondrial network [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a hypomorphic mutation in PCYT2 (a component of the CDP-ethanolamine pathway) was shown to cause recessive forms of progressive neurodegeneration, namely spastic paraplegia disorders [ 7 ]. Homozygous mutations in PSD genes cause a range of conditions, including skeletal dysplasia, early-onset retinal degeneration, hearing loss, microcephaly, and intellectual disability [ 20 22 ]. It is clear therefore that both PE biosynthesis pathways are crucial for the function and survival of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The encoding proteins of those disease-causing genes have diverse functions involving different signaling pathways, such as NOTCH, BMP, or TGFβ signaling, which are essential for skeletal development, growth, or homeostasis ( Krakow, 2015 ). Interestingly, some pathogenic variants in mitochondrial-associated proteins have been shown to cause skeletal dysplasias, which is not common for mitochondria-related disorders ( Mehawej et al, 2014 ; Dikoglu et al, 2015 ; Girisha et al, 2019 ; Peter et al, 2019 ). In addition to the protein-coding gene, the epigenetic alteration, first included in 2019 Nosology, indicates a novel gain-of-function variant in microRNA miR-140, which causes autosomal dominant skeletal dysplasia ( Grigelioniene et al, 2019 ; Mortier et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%